PARTISIPASI MASYARAKAT DALAM PELESTARIAN HUTAN MANGROVE DI PESISIR TANGKOLAK DESA SUKAKERTA KECAMATAN CILAMAYA WETAN KABUPATEN KARAWANG - Pramudya Duta Harsono; Slamet Abadi; Kuswarini Sulandjari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The destruction of mangrove forests in Indonesia is increasing over time. Preservation of mangrove forests is needed to maintain the mangrove forest ecosystem so that it can support the lives of coastal communities in environmental, social and economic aspects. The participation of coastal communities is very necessary in helping the success of existing conservation. The purpose of this study was to identify the form, level driving, and inhibit community participation in the conservation of mangrove forests in Tangkolak Hamlet, Sukakerta Village. This research is a quantitative and qualitative research. Data analysis using the method: Likert scale, score, and descriptive. The results showed that community participation in the form of ideas (78.46%), energy (63.08), property (98.46%), and skills (76.92%) were included in the low category with a combined score (81. 54%). Community participation was at the consultation level (score 394 based on Sherry Arnstein's theory). The driving factors consist of a sense of responsibility, the benefits of mangrove forests, self-awareness, and an invitation. Inhibiting factors consist of work, laziness, the role of the community is considered unimportant, and there is no invitation. There is an increase in the form of participation, it is necessary to involve the community in all process activities, and there is counseling to the community about mangrove forest conservation.